Structure–activity correlation in aerobic cyclohexene oxidation and peroxide decomposition over CoxFe3−xO4 spinel oxides. Issue 11 (25th April 2022) - Büker, Julia; Angel, Steven; Salamon, Soma; Landers, Joachim; Falk, Tobias; Wende, Heiko; Wiggers, Hartmut; Schulz, Christof; Muhler, Martin; Peng, Baoxiang
Abstract : Aerobic cyclohexene oxidation and peroxide decomposition in the liquid phase were performed over a series of Co x Fe3− x O4 spinel catalysts exhibiting a volcano plot for the catalytic activity with a maximum at x = 1. Abstract : Nanoparticulate Co x Fe3− x O4 (0 ≤ x ≤ 3) catalysts were prepared by spray-flame synthesis and applied in liquid-phase cyclohexene oxidation with O2 as oxidant. The catalysts were characterized in detail using N2 physisorption, XRD, TEM, XPS, FTIR, Raman, and Mössbauer spectroscopy. A volcano plot was obtained for the catalytic activity in cyclohexene oxidation as a function of the Co content with a maximum at x = 1. Thus, CoFe2 O4 achieved the highest degree of cyclohexene conversion and the fastest decomposition rate of the key intermediate 2-cyclohexene-1-hydroperoxide. Kinetic studies and a stability test were performed over CoFe2 O4, showing that cyclohexene oxidation follows first-order kinetics with an apparent activation energy of 58 kJ mol −1 . The catalytic hydroperoxide decomposition during cyclohexene oxidation was further investigated using H2 O2 and tert -butyl hydroperoxide as simpler surrogates resulting in similar volcano-type correlations. The increase in catalytic activity with increasing Fe content with a maximum at x = 1 is ascribed to the increasing concentration of octahedrally coordinated Co 2+ cations in the spinel structure leading to the presence of coordinatively unsaturated Co3c 2+ surface sites, which are identified to be the most active sites for 2-cyclohexene-1-hydroperoxide decomposition in cyclohexene oxidation.